مفهوم جزاء الأعمال عند البوذية والإسلام : دراسة مقارنة بين النرفانا والجنة - Qutub Shah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study focuses on the concept of reward of human deeds in Buddhism and Islam, and the comparison between nirvana of Buddhism and jannah (paradise) of Islam as the ultimate reward of human good deeds. The study first discussed the reward system of human deeds in both Buddhism and Islam in general, and especially nirvana and jannah. Then it compared between the two ideas in terms of significance, nature, and the way, to find the similarities and differences. The methodology adopted by the thesis is descriptive, analytical and comparative based on the scriptures and available literatures. The most important findings by the study are as follows: necessity of belief in the ultimate reward of human deeds; inevitability of revelation to know the reality of supra-mundane things; both are believed to be the ultimate goal of life, supreme bliss and happiness, and final destination of human; jannah, its bliss and life are material, sensual and spiritual unlike nirvana, perception of its reality depends on personal experience, but is considered bliss due to the lack of sufferings; the way to nirvana is extreme asceticism, while that of paradise is moderate between deen and dunya; contrary to Buddhism and its nirvana, the deeds in Islam are to worship Allah to please Him, and jannah is His reward of satisfaction; and the Buddhist reward system is less influential than that of Islam.